The Role of a Critical Time Intervention on the Experience of Continuity of Care Among Persons With Severe Mental Illness After Hospital Discharge. Issue 1 (January 2015) - Tomita, Andrew; Herman, Daniel B.
<x xml:space="preserve">Abstract</x> Abstract We investigated the impact of critical time intervention (CTI) on self-reported indicators of quality of continuity of care (COC) after discharge from inpatient psychiatric treatment with data from a randomized controlled trial that assessed the effectiveness of the intervention in reducing recurrent homelessness. Postdischarge COC outcome measures among previously homeless persons with severe mental illness randomly assigned to receive usual services only (n = 73) or 9 months of CTI in addition to usual services (n = 77) were compared. Those assigned to CTI had greater perceived access to care than the usual services group did, with this impact extending beyond the point at which the intervention ended. A time-limited care coordination intervention provided immediately after hospital discharge may improve COC, but further studies are needed to substantiate an effect of CTI on long-term continuity outcomes.